2003
DOI: 10.1103/physrevlett.90.095701
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation Lines as the Precursor of the Melting of Crystalline Solids Observed in Monte Carlo Simulations

Abstract: The microscopic mechanism of the melting of a crystal is analyzed by the constant pressure Monte Carlo simulation of a Lennard-Jones fcc system. Beyond a temperature of the order of 0.8 of the melting temperature, we found that the relevant excitations are lines of defects. Each of these lines has the structure of a random walk of various lengths on an fcc defect lattice. We identify these lines with the dislocation ones proposed in recent phenomenological theories of melting. Near melting we find the appearan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 15 publications
(17 reference statements)
4
86
0
Order By: Relevance
“…The influence of interatomic distance fluctuations on the nature of the phase transitions in this model will be addressed in a future study. Finally, let us note that while it is known that the solid phase cannot survive at finite T in two dimensions with continuous degrees of freedom of atom motions, our present study with discrete degrees of freedom shows some interesting behaviors which would serve as a starting point to study three-dimensional solids where melting mechanisms are not well understood [1,2]. ACKNOWLEDGMENT M.K.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of interatomic distance fluctuations on the nature of the phase transitions in this model will be addressed in a future study. Finally, let us note that while it is known that the solid phase cannot survive at finite T in two dimensions with continuous degrees of freedom of atom motions, our present study with discrete degrees of freedom shows some interesting behaviors which would serve as a starting point to study three-dimensional solids where melting mechanisms are not well understood [1,2]. ACKNOWLEDGMENT M.K.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical properties of solids, such as melting [1,2] and mechanical failure [3][4][5][6], are topics of considerable interest. In this paper we continue the analysis of an equilibrium statistical mechanics model [7,8] of a solid.…”
Section: Introductionmentioning
confidence: 99%
“…Such loops, with lifetimes on the order of 20 ps, roughly correspond to Shockley partial dislocations surrounding stacking faults. 37 The loops on the Ni side of the Ni-Zr interface are seen to glide mainly along the ͓101͔ and ͓110͔ crystallographic directions. On the Zr side of the interface, the loops glide instead mainly along the ͓110͔ and ͓210͔ crystallographic directions.…”
Section: Defective Atoms and Lattice Defectsmentioning
confidence: 99%
“…More recently, melting has been investigated by Monte Carlo computer simulations [10][11][12]. Gomez et al [11,12] evaluated the percentage of defects near TM and showed that defects form clusters, which are not isolated, but rather linked over long distances near the phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…Gomez et al [11,12] evaluated the percentage of defects near TM and showed that defects form clusters, which are not isolated, but rather linked over long distances near the phase transition. In fact, their calculations indicate that the linked clusters are dislocations and melting is consistent with the saturation of the crystal by dislocation loops.…”
Section: Introductionmentioning
confidence: 99%